A Preliminary Examination of Motivating Operation and Reinforcer Class Interaction. (13th November 2015) - Ivy, Jonathan W.; Neef, Nancy A.; Meindl, James N.; Miller, Neal
Abstract : The interaction effects between motivating operations and reinforcer classes were evaluated using a superordinate multielement design. Two individuals with developmental disabilities participated. Participants were exposed to a motivating operation condition—pre‐session access until rejection or pre‐session restriction for 24 h—followed by a reinforcer assessment, in which the reinforcer response requirements progressively increased. Reinforcers, stimuli representative of primary, conditioned, and token reinforcers, were available on alternating sessions. The results showed that pre‐session access and restriction produced reliable evocative and abative effects across reinforcer classes. For one of the participants, the effectiveness of the motivating operation appeared to be influenced by the reinforcer class. The interaction effects between motivating operations and reinforcer classes are discussed. Copyright © 2015 John Wiley & Sons, Ltd.